Building The Spirit Of Leadership Among Mu’allim (Case Study of the ISMI Organization at TMI Putra Al-Amien Prenduan) - Amrul; Totok Agus Suryanto; Mudiuddin (Penerbit Hellow Pustaka, 2025)
Leadership is a process that must exist and be developed in human life as social beings. An individual's leadership potential can be cultivated from an early age, whether in the family environment or at school, and each school typically has internal organizations for its students. The Association of Tarbiyatul Mu’allimien Students (ISMI) is an active organization within the TMI Al-Amien Prenduan Islamic boarding school (ma’had), consisting of senior students, also referred to as mu’allim. A mu’allim serves as one of the right-hand aides to the kyai (Islamic scholar or leader) in the pesantren, and also functions as an administrator and leader for other students. The issue examined in this study is focused on one main question: What forms of guidance are provided to the mu’allim in developing leadership spirit? This research is a field study with a qualitative descriptive approach. Data collection techniques employed triangulation methods, including interviews, observation, and documentation. The researcher then analyzed the data and information obtained from informants to extract findings aligned with the research focus. To verify the validity of the data, cross-triangulation was applied by comparing interview results with observations—contrasting the informants' perspectives with the researcher’s direct findings. The results of this study indicate that (1) the guidance provided by the Tarbiyatul Mu’allimien Al-Islamiyah boarding school has been implemented effectively and leads toward positive outcomes. The support given to mu’allim includes several forms of assistance, such as: leadership training for student group leaders, basic-level skill training courses, leadership and management training, and the establishment of a consultant staff team.